2020
DOI: 10.1111/bjh.16477
|View full text |Cite
|
Sign up to set email alerts
|

Lycorine targets multiple myeloma stem cell‐like cells by inhibition of Wnt/β‐catenin pathway

Abstract: Summary Multiple myeloma (MM) is characterised by the proliferation and accumulation of malignant plasma cells in the bone marrow. Despite the progress in treatment over the last few years, MM remains incurable and the majority of patients relapse. MM stem‐like cells (MMSCs) have been considered as the main reason for drug resistance and eventual relapse. Currently, therapeutic agents are not enough to eradicate MMSCs, and finding effective strategies to eradicate MMSCs may improve the outcome of patients. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 45 publications
2
16
0
Order By: Relevance
“…Therefore, the chemical structure of lycorine was used as natural lead for further drug development. Wang et al investigated the effect of lycorine on myeloma cell lines ARP1, KMS11, ANBL6, and ANBL6 and found that the compound inhibited proliferation by decreasing ALDH1 + cells, which are supposed to be cancer stem cells [ 28 ]. Furthermore, lycorine was found to act via the Wnt/β-catenin pathway by lowering β-catenin protein levels and to exhibit synergistic effects when combined with bortezomib.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the chemical structure of lycorine was used as natural lead for further drug development. Wang et al investigated the effect of lycorine on myeloma cell lines ARP1, KMS11, ANBL6, and ANBL6 and found that the compound inhibited proliferation by decreasing ALDH1 + cells, which are supposed to be cancer stem cells [ 28 ]. Furthermore, lycorine was found to act via the Wnt/β-catenin pathway by lowering β-catenin protein levels and to exhibit synergistic effects when combined with bortezomib.…”
Section: Resultsmentioning
confidence: 99%
“…ALDH1A1 is the dominant isoform in MM; when the expression of ALDH1A1 in ARP1 and OPM1 cells was driven by a lentivirus vector, the cells showed resistance to bortezomib and adriamycin [ 41 ]. In BTZ-resistant (ANBL6-BR) cells, ALDH1 + cells constitute a larger proportion of the population than in wild-type (ANBL6) cells, and ALDH1A1 is highly expressed in BTZ-resistant cells [ 42 ]. ALDH-activity detection has been used to reflect the stemness of MM cells in the study of drug killing-effect detection, surface markers, and characteristic proteins identification in the MM stem cell-like population [ 18 , 43 , 44 , 45 ]…”
Section: Markers Of Mmscs and Drugs Targeting Themmentioning
confidence: 99%
“…Additionally, wee1 kinase inhibitor MK1775 can significantly decrease the rate of ALDH1 + cells. Surprisingly, proteasome inhibitor BTZ can enhance the percent of ALDH1 + cells in glioblastoma, synovial sarcoma, pancreatic adenocarcinoma, and MM cells [ 42 , 50 ]. Furthermore, lycorine or wee1 kinase inhibitor MK1775 can decrease the rate of ALDH1 + cells in combination with BTZ [ 35 , 42 ].…”
Section: Markers Of Mmscs and Drugs Targeting Themmentioning
confidence: 99%
See 2 more Smart Citations